Narrative Review: Parameter dalam Metode Analisis untuk Identifikasi Rhodamin B dalam Lipstik - Nurlita Dwi Putri Prihasti; Munir Alinu Mulki; Muhammad Naufal Nurhadi Hidayat (Jurnal Sehat Mandiri, 2024)
Rhodamine B is a synthetic dye used in the paper and textile industries, attracting attention due to its potential health hazards. It is used in various cosmetic products, although the Regulation of the Minister of Health of Indonesia No. 445/MENKES/PER/V/1998 prohibits its use in cosmetics due to risks of irritation, liver damage, and cancer. This article reviews the parameters of analytical methods for identifying Rhodamine B in lipstick. A narrative review was conducted using Google Scholar as a database over the past 10 years. The KLT method was found to be more widely used than HPLC or UV-Vis Spectrophotometry. Differences in Rf values in KLT are due to variations in the stationary phase. Parameter variations in HPLC system suitability tests are caused by operational conditions, sample conditions, and instrument performance. Analytical methods for identifying Rhodamine B in lipstick include KLT, HPLC/KCKT, and UV-Vis Spectrophotometry. It is concluded that each method has specific parameters that must be met: KLT is qualified if the Rf value comparison (standard vs. sample) is ≤ 0.2; HPLC/KCKT requires system suitability and validation tests; UV-Vis Spectrophotometry needs validation test parameters. KLT is preferred due to easy sample preparation and lower costs compared to HPLC and UV-Vis Spectrophotometry. It is recommended to consider necessary components when using these methods to maximize test results.